2019
DOI: 10.2478/eje-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of actinobacteria in the marshes of Ezzemoul and Djendli in northeastern Algeria

Abstract: The main purpose of this research is to study the microbial diversity of actinobacteria, living in "Ezzemoul" and "Djendli" sebkhas soils. These salt lakes are situated in the east of Algeria and they are microbiologically underexploited. Such unexplored ecological niches have been considered by many authors as sources of novel actinobacteria and bioactive molecules. Actinobacteria play an important role in safeguarding the environment by improving plant growth through nitrogen fixation, biodegradation, and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Our previous studies have shown that several actinomycetes isolated from Algerian saline soils (salt tolerance up to 10% (i.e., 1.7 M)) [29] have good in vitro and in planta (Solanum lycopersicum L.) plant growth-promoting (PGP) traits under normal conditions [30]. In this study, we advanced the hypothesis that these strains could be valid agents to salt stress tolerance.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our previous studies have shown that several actinomycetes isolated from Algerian saline soils (salt tolerance up to 10% (i.e., 1.7 M)) [29] have good in vitro and in planta (Solanum lycopersicum L.) plant growth-promoting (PGP) traits under normal conditions [30]. In this study, we advanced the hypothesis that these strains could be valid agents to salt stress tolerance.…”
Section: Introductionmentioning
confidence: 85%
“…The actinomycetes strains were isolated from two saline sites in the northeast region of Algeria, Ezzemoul sebkha-35 • 53 14 North; 06 • 30 20 East; pH 8.6; EC (electrical conductivity) 1600 µS cm −1 ; organic matter 6.0%; moisture and organic matter 6.0%; sand 52.8%; slit 22.4%; clay 24.8%-and Djendli sebkha-35 • 43 15 North; 06 • 32 23 East; pH 8.0; EC 1101 µS cm −1 ; organic matter 6.2%; moisture and organic matter 5.8%, sand 31.0%; slit 32.7%; clay 36.3% [29,30]. The soil samples were taken according to the Pochon and Tardieux method [31].…”
Section: Actinomycetes Strainsmentioning
confidence: 99%
“…Based on these results, among the 60 strains tested, 14 strains were selected as promising PGPB: These isolates tolerated up to 10% NaCl during in vitro testing, suggesting halotolerant traits [25].…”
Section: Plant-growth-promoting Traitsmentioning
confidence: 99%
“…The following fourteen strains of actinomycetes, previously isolated and characterized [62], were used in this study:…”
Section: Methodsmentioning
confidence: 99%